Serum Copper and Plasma Protein Status in Preterm Delivery - Sultana, Masuda; Jahan, Nasim; Sultana, Nayma; Akter, Rezina (Journal of Bangladesh Society of Physiologist, 2012)
Background: Preterm delivery is a major obstetric related problem in Bangladesh. Micronutrient deficiency especially deficiency of copper may affect pregnancy, delivery and outcome of pregnancy. Reduced serum copper concentration of the pregnant mother may have some role in resulting preterm delivery. Objectives: To observe serum Cu and protein status in preterm mother and their neonates. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, between January and December 2009. A total number of 136 subjects were included in this study, and were divided into control (n=82) and study (n=54) groups. Of the control group, 28 were non pregnant women age ranged between 20-30 years, taken for reference value and another 54 were full term group, also treated as control, were sub-divided into normal full term mother (n=27) and their respective neonates ( n=27). Another 54 were preterm group, considered as study group, were sub-divided into preterm mothers (n=27) and their respective neonates (n=27). Age of preterm and full term mothers were between 20-40 years. All the subjects belonged to lower socioeconomic status. The pregnant women were selected from the labor ward of Sir Salimullah Medical College and Mitford Hospital and non pregnant women were from personal contact. Serum copper level was estimated by spectrophotometric method, to observe its level in these groups of study subjects. Serum total protein, albumin and globulin levels were estimated by usual laboratory technique in order to observe the availability of binding proteins as well as their nutritional status. Again, anthropometric data and blood hemoglobin level of the preterm and full term mother and birth weight of their respective neonates were measured to observe their nutritional status. Correlation of maternal serum copper concentration with that of neonatal blood and also with birth weight of the neonates were done to observe their relationship. Statistical analysis was done by Independent-Samples t test and Peaesons correlation coefficient tests as applicable. Results: Mean serum Cu, total protein and albumin levels were significantly (p<0.001) lower in preterm mother and their neonates in comparison to those of full term mother and their neonates respectively. Whereas, mean serum globulin level showed no statistically significant difference among the groups. Mean birth weight of preterm neonates was significantly lower in comparison to that of full term neonates. Again, maternal serum copper level showed negative correlation with that of neonatal blood but positive correlation with birth weight of their neonates in both full term and preterm mother, though these relationships were not statistically significant. Conclusions: The present study revealed hypocupremia and hypoproteinemia in pre-term delivery mother and their neonates. This hypocupremia may be due to poor maternal protein status. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11161 J Bangladesh Soc Physiol. 2012, June; 7(1): 41-47